2018
DOI: 10.1016/j.neuroscience.2018.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Systemic or Forebrain Neuron-Specific Deficiency of Geranylgeranyltransferase-1 Impairs Synaptic Plasticity and Reduces Dendritic Spine Density

Abstract: Isoprenoids and prenylated proteins regulate a variety of cellular functions, including neurite growth and synaptic plasticity. Importantly, they are implicated in the pathogenesis of several diseases, including Alzheimer's disease (AD). Recently, we have shown that two protein prenyltransferases, farnesyltransferase (FT) and geranylgeranyltransferase-1 (GGT), have differential effects in a mouse model of AD. Haplodeficiency of either FT or GGT attenuates amyloid-β deposition and neuroinflammation but only red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
(92 reference statements)
2
14
0
Order By: Relevance
“…Using a genetic approach, we have demonstrated recently that reduction of FTase, but not GGTase-I, ameliorates spatial learning and memory as well as attenuates Aβ deposition and neuroinflammation in APP/PS1 mice (Cheng et al, 2013). In a more recent study, we have observed that systemic or forebrain neuron specific deficiency of GGTase-I reduces dendritic spine density and impairs synaptic/cognitive function in wild type mice (Hottman et al, 2018), corroborating the critical role of GGTase-I and protein geranylgeranylation in neuronal structure and function suggested by previous studies (Gao, Yu, and Zhou, 2016; Zhou et al, 2008). These findings suggest that farnesylated and geranylgeranylated proteins play distinctive roles in the pathogenesis of AD.…”
Section: Connections Between Isoprenoids/protein Prenylation and Alzhsupporting
confidence: 86%
“…Using a genetic approach, we have demonstrated recently that reduction of FTase, but not GGTase-I, ameliorates spatial learning and memory as well as attenuates Aβ deposition and neuroinflammation in APP/PS1 mice (Cheng et al, 2013). In a more recent study, we have observed that systemic or forebrain neuron specific deficiency of GGTase-I reduces dendritic spine density and impairs synaptic/cognitive function in wild type mice (Hottman et al, 2018), corroborating the critical role of GGTase-I and protein geranylgeranylation in neuronal structure and function suggested by previous studies (Gao, Yu, and Zhou, 2016; Zhou et al, 2008). These findings suggest that farnesylated and geranylgeranylated proteins play distinctive roles in the pathogenesis of AD.…”
Section: Connections Between Isoprenoids/protein Prenylation and Alzhsupporting
confidence: 86%
“…We suggested that the downregulation of GGTase-Iβ may be one of the mechanisms that cause age-related weakening of synaptic plasticity (Afshordel et al 2014 ). Directly related to our findings Hottman et al recently published that systemic or forebrain neuron-specific deficiency of GGTase-I reduces dendritic spine density and impairs synaptic plasticity in the brains of young adult mice, concurrently with reduced geranylgeranylation of Rho proteins (Hottman et al 2018 ).…”
Section: Introductionsupporting
confidence: 88%
“…In vitro GGTase-I inhibition mimicked the changes we observed in the brain of aged mice, including a decreased frequency of synaptic markers (Afshordel et al 2014 ). That GGTase-I deficiency leads a significant decrease in cortical spine density and cognitive function has been recently shown in GGT-haplodeficient mice (Hottman et al 2018 ). Using a conditional forebrain neuron-specific GGT knockout they further demonstrated a decrease of both the magnitude of hippocampal LTP and the dendritic spine density of cortical neurons in those mice (Hottman et al 2018 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations